2013
DOI: 10.1063/1.4810879
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Substrate induced dehydrogenation: Transformation of octa-ethyl-porphyrin into tetra-benzo-porphyrin

Abstract: Faculty of Physics and Center for Nanointegration Duisburg-Essen (CENIDE), University of 47048 Duisburg, Germany (Received 27 March 2013; accepted 29 May 2013; published online 7 June 2013) Individual molecules of octa-ethyl-porhphyrin-iron(III)-chloride adsorbed on a Cu(111) surface are studied by scanning tunneling microscopy. Upon moderate heating the molecules are found to transform into Fe-tetra-benzo-porphyrin at a surprisingly low temperature of 380 K. If the annealing is interrupted, the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…These changes, taken together, indicate a chemical transformation of the peripheral ethyl groups to aromatic benzo groups, i.e., a dehydrocyclization (Scheme 1). The temperature of 500 K is consistent with other studies of dehydrogenation of ethyl groups and C-H bond scission on Cu and other surfaces [59,83]. The dehydrocyclization of OEP on Cu(100) at 500 K (15 minute anneal) ( Fig.…”
Section: Dehydrocyclization Of Oep On Cu(100) and On Ag(111)supporting
confidence: 89%
See 3 more Smart Citations
“…These changes, taken together, indicate a chemical transformation of the peripheral ethyl groups to aromatic benzo groups, i.e., a dehydrocyclization (Scheme 1). The temperature of 500 K is consistent with other studies of dehydrogenation of ethyl groups and C-H bond scission on Cu and other surfaces [59,83]. The dehydrocyclization of OEP on Cu(100) at 500 K (15 minute anneal) ( Fig.…”
Section: Dehydrocyclization Of Oep On Cu(100) and On Ag(111)supporting
confidence: 89%
“…The dehydrocyclization of OEP on Cu(100) at 500 K (15 minute anneal) ( Fig. 2) is higher in temperature than a previous report for the dehydrocyclization of Fe-OEP on Cu(111) at 430 K (60 minute anneal) [59].…”
Section: Dehydrocyclization Of Oep On Cu(100) and On Ag(111)mentioning
confidence: 51%
See 2 more Smart Citations
“…47 Moreover, Vörden et al demonstrated that the Cu(111) surface induced the transformation of octa-ethyl-porphyrin to tetra-benzo-porphyrin with an activation energy of B1.2 eV. 48 Most relevant are the findings by Xiao et al,…”
Section: Resultsmentioning
confidence: 90%